2020
DOI: 10.1038/s41524-020-0340-7
|View full text |Cite
|
Sign up to set email alerts
|

Pores for thought: generative adversarial networks for stochastic reconstruction of 3D multi-phase electrode microstructures with periodic boundaries

Abstract: The generation of multiphase porous electrode microstructures is a critical step in the optimisation of electrochemical energy storage devices. This work implements a deep convolutional generative adversarial network (DC-GAN) for generating realistic nphase microstructural data. The same network architecture is successfully applied to two very different three-phase microstructures: A lithium-ion battery cathode and a solid oxide fuel cell anode. A comparison between the real and synthetic data is performed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(93 citation statements)
references
References 53 publications
0
93
0
Order By: Relevance
“…Recently, Gayon‐Lombardo et al. [ 78 ] proposed to use periodic boundaries instead of Dirichlet boundaries for the diffusion‐based method for the conventional tortuosity factor determination. They suggested that this approach allowed representing better the bulk behavior of the microstructure.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Gayon‐Lombardo et al. [ 78 ] proposed to use periodic boundaries instead of Dirichlet boundaries for the diffusion‐based method for the conventional tortuosity factor determination. They suggested that this approach allowed representing better the bulk behavior of the microstructure.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, following segmentation, Generative Adversarial Networks (GANs) are now being developed to learn the phase arrangement in segmented data and generate mesostructure realizations with customized properties in volumes larger than could be obtained from imaging alone ( Figure 3 e,f). 43 …”
Section: Accurate 3d Mesostructuresmentioning
confidence: 99%
“…[168][169][170][171][172][173][174][175] In conjunction with the experimental techniques and mathematical models introduced in Section 3, AI techniques have been successfully employed in the study of energy materials. Various machine learning (ML) methods and advanced deep neural networks (DNN) have shown excellent performance in regard to material structure reconstruction and generation, and property and performance prediction, such as artificial neural networks (ANN), 174 support vector machines (SVM), 176 convolutional neural networks (CNN), [177][178][179][180][181][182] generative adversarial neural networks (GANN) [183][184][185][186][187][188][189][190] and so on. Fig.…”
Section: The Future Of Energy Materials: Digitalisation Of Porous Enementioning
confidence: 99%